African American Women in the Workplace: Models of Career Development - Delores Rice (Adult Education Research Conference, 2010)
Research and literature addressing the career development of African American women in the workplace are scant, relative to the dominant group whose patterns of work and living are generalized to those of Black women. This session will discuss and critique traditional theories of career development and their relevance to our understanding of Black women's career development in White dominated organizations. Current emerging and more appropriate models will also be discussed.